2013
DOI: 10.1038/cr.2013.31
|View full text |Cite
|
Sign up to set email alerts
|

Single strand DNA binding proteins 1 and 2 protect newly replicated telomeres

Abstract: Human single-strand (ss) DNA binding proteins 1 and 2 (hSSB1 and 2) are components of the hSSB1/2-INTS3-C9orf80 heterotrimeric protein complex shown to participate in DNA damage response and maintenance of genome stability. However, their roles at telomeres remain unknown. Here, we generated murine SSB1 conditional knockout mice and cells and found that mSSB1 plays a critical role in telomere end protection. Both mSSB1 and mSSB2 localize to a subset of telomeres and are required to repair TRF2-deficient telome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
58
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(61 citation statements)
references
References 35 publications
3
58
0
Order By: Relevance
“…Strikingly, all three studies reported pronounced upregulation of Ssb2 in response to Ssb1 deletion in both Ssb1 −/− tissues and MEFs [6][7][8]. Given that Ssb2 can substitute for Ssb1 in INTS3-SSB-C9Orf80 complexes, these results suggest that Ssb2 may compensate for some roles of Ssb1.…”
mentioning
confidence: 74%
See 4 more Smart Citations
“…Strikingly, all three studies reported pronounced upregulation of Ssb2 in response to Ssb1 deletion in both Ssb1 −/− tissues and MEFs [6][7][8]. Given that Ssb2 can substitute for Ssb1 in INTS3-SSB-C9Orf80 complexes, these results suggest that Ssb2 may compensate for some roles of Ssb1.…”
mentioning
confidence: 74%
“…Given that Ssb2 can substitute for Ssb1 in INTS3-SSB-C9Orf80 complexes, these results suggest that Ssb2 may compensate for some roles of Ssb1. However, attempts to deplete Ssb2 even in wild-type MEFs led to rapid cell death, indicating that Ssb2 may play additional roles critical for cell viability [6,7]. The study by Gu et al [7] elegantly circumvented these effects through reconstitution of Ssb1 −/− MEFs with a mutant Ssb1 construct that does not result in concomitant upregulation of Ssb2.…”
mentioning
confidence: 99%
See 3 more Smart Citations